Surveillance assessment Ms Iso17025:2017 by Jabatan Standard Malaysia / Kathleen J.Jalani and Dr. John Shia Kwong Siew - J.Jalani, Kathleen; John Shia, Kwong Siew (Faculty of Pharmacy, 2023)
UiTM Pharmacy Analytical Laboratory (UiPAL) has successfully undergone MS ISO/IEC 17025:2017 surveillance assessment conducted by Jabatan Standard Malaysia (JSM) on 10th February 2023. MS ISO ISO/IEC 17025:2017 emphasizes on the general requirement for the analysis according to the Standard Malaysia to carry out tests and/or calibrations as well as sampling. The assessment is carried out annually to ensure all laboratory activities were carried out according to the standard, thus continuing the MS ISO/IEC 17025 certification for the laboratory.